2013
DOI: 10.4103/1947-2714.114171
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intake and the presence of the metabolic syndrome

Abstract: Background:Dietary micronutrients have been proposed to protect against oxidative damage and related clinical complications.Aims:We aimed to compare the micronutrient intake between individuals with and without metabolic syndrome (MS).Materials and Methods:This cross-sectional study included 3800 men and women who were aged between 35 and 65 years. The diagnosis of the MS was based on International Diabetes Federation criteria. Dietary intake of participants was assessed using a questionnaire for 24 h dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 33 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Ford et al [ 14 ] concluded that subjects with MS had a significantly lower level of dietary vitamin A intake, but the total carotenoid intake was similar in the two compared groups; Zulet et al also suggested that vitamin A intake was related to several anthropometrical and biochemical measurements that were linked to MS manifestations in healthy young adults, but they did not evaluate the association between pro-vitamin A intake and MS. [ 33 ] Our study also found no significant association between dietary vitamin E intake and MS, and this conclusion is consistent with several former studies [ 14 , 21 ]. Several other epidemiological studies did not find a significant association between dietary antioxidants intake and MS: Bian et al [ 11 ] demonstrated that there was no negative correlation between the dietary antioxidant vitamins group and MS, Motamed et al [ 13 ] and Li et al [ 12 ] also found no significant association between dietary antioxidant intake and MS. Additionally, a few studies have suggested that antioxidant supplementation had no beneficial effects on MS [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ford et al [ 14 ] concluded that subjects with MS had a significantly lower level of dietary vitamin A intake, but the total carotenoid intake was similar in the two compared groups; Zulet et al also suggested that vitamin A intake was related to several anthropometrical and biochemical measurements that were linked to MS manifestations in healthy young adults, but they did not evaluate the association between pro-vitamin A intake and MS. [ 33 ] Our study also found no significant association between dietary vitamin E intake and MS, and this conclusion is consistent with several former studies [ 14 , 21 ]. Several other epidemiological studies did not find a significant association between dietary antioxidants intake and MS: Bian et al [ 11 ] demonstrated that there was no negative correlation between the dietary antioxidant vitamins group and MS, Motamed et al [ 13 ] and Li et al [ 12 ] also found no significant association between dietary antioxidant intake and MS. Additionally, a few studies have suggested that antioxidant supplementation had no beneficial effects on MS [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 10 ] A limited number of studies [ 11 14 ] have explored the relationship between dietary antioxidants intake and MS, but the conclusions have been inconsistent. Puchau et al [ 8 ] suggested that total dietary antioxidant capacity may be a potential early indicator in those at risk of developing MS. Bian et al [ 11 ], Li et al [ 12 ] and Motamed et al [ 13 ] all denied the existence of a significant relationship between dietary antioxidants intake and MS. However, the studies of Bian et al [ 11 ] and Li et al [ 12 ] had small sample size (258 and 550 subjects, respectively), while the results from Li et al were only adjusted for age and sex.…”
Section: Introductionmentioning
confidence: 99%
“…However, findings regarding the association between antioxidant intake and the development of MS remain inconsistent. Wei et al [13] and Motamed et al [49] did not observe a significant association between the intake of vitamins A and E and the development of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from animal models has indicated a fundamental interplay between micronutrients and metabolic physiology with implications for health and disease 1 , 2 . An impaired energetic metabolism is often accompanied by a shortage of cellular energy supply and vice versa.…”
Section: Introductionmentioning
confidence: 99%